Dramaturgy : a revolution in theatre - Luckhurst, Mary (Cambridge studies in modern theatre., 2006)
"[This book] is the first substantial history of the origins of dramaturgs and literary managers. It frames the recent explosion of professional appointments in England within a wider continental map reaching back to the Enlightenment and eighteenth-century Germany, examining the work of the major theorists and practitioners of dramaturgy, from Granville Barker and Gotthold Lessing to Brecht and Tynan. This study is the first to position Brecht's model of dramaturgy as central to the world-wide revolution in theatre-making practices, and is also the first work to make a substantial argument for Granville Barker's and Tynan's contributions to the development of literary management today. With the territories of play and performance-making being increasingly hotly contested, and the public's appetite for new plays shows no sign of diminishing, Mary Luckhurst investigates the dramaturg as a cultural and political phenomenon."--Publisher's description, from p. [2] of book jacket